Development of an interactive heyzine flipbook e-module for ipas with a deep learning approach in elementary schools - Faizal; Khoirunnisa; Hendra Budiono; Violita Zahyuni; Michael Escaros Mananghaya (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This research aims to develop an interactive e-module using Heyzine flipbook integrated with a deep learning approach for the IPAS (Science and Social Studies) subject in elementary schools. The deep learning approach in this study refers to a pedagogical strategy that emphasizes conceptual understanding, meaningful learning, and active student engagement. The e-module was developed using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Validity was assessed by three experts (media, content, and language) using a Likert-scale questionnaire, while practicality was evaluated by one teacher and 26 fourth-grade students through response questionnaires. The results showed an average validity score of 4.7 (highly valid) and an average practicality score of 4.69 (highly practical). Based on these findings, the developed e-module is declared valid and practical, thus feasible for use in the learning process. Further research is needed to examine its effectiveness in improving student learning outcomes.